2020
DOI: 10.1038/s41598-020-71410-2
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of hydrate-bound gas retrieved at the Kedr mud volcano (southern Lake Baikal)

Abstract: We reported the characteristics of hydrate-bound hydrocarbons in lake-bottom sediments at the Kedr mud volcano in Lake Baikal. Twenty hydrate-bearing sediment cores were retrieved, and methane-stable isotopes of hydrate-bound gases (δ13C and δ2H of − 47.8‰ to − 44.0‰ V-PDB and − 280.5‰ to − 272.8‰ V-SMOW, respectively) indicated their thermogenic origin accompanied with secondary microbial methane. Powder X-ray diffraction patterns of the crystals and molecular composition of the hydrate-bound gases suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Since CO 2 comprises carbon and oxygen atoms, several isotopic species of CO 2 exist, depending on the combination of stable isotopes (isotopologues: 12 C, 13 C, 16 O, 17 O, and 18 O). For example, the abundance ratio of 13 CO 2 is~1.1% of the total CO 2 and the rest is almost 12 CO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since CO 2 comprises carbon and oxygen atoms, several isotopic species of CO 2 exist, depending on the combination of stable isotopes (isotopologues: 12 C, 13 C, 16 O, 17 O, and 18 O). For example, the abundance ratio of 13 CO 2 is~1.1% of the total CO 2 and the rest is almost 12 CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the trend of hydrogen and carbon isotope fractionation during the formation of synthetic methane and ethane hydrates was Molecules 2021, 26, 4215 2 of 8 investigated [13]. Moreover, the results were applied to estimate the formation process of natural gas hydrates [14][15][16]. Carbon isotope fractionation during the formation of CO 2 hydrates was reported [17], revealing that the CO 2 δ 13 C in the hydrate phase was 0.9‰ lower than that in the gas phase at 268 K [17].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, little-to-no carbon isotope fractionation (the difference in δ 13 C between encapsulated and residual CH 4 ) was observed. Isotopic fractionation for ethane hydrate and CO 2 hydrate , was also investigated. These results for synthetic CH 4 hydrates were used as a reference for estimating the formation process of a natural gas hydrate by comparing the isotopic data for hydrate-bound and dissolved gas in the lake/sea bottom sediment. …”
Section: Introductionmentioning
confidence: 99%
“…Gas hydrates and authigenic carbonates were detected in sediments of the MV Kedr. It was also shown that the area around the MV has moundy bottom relief with pockmarks, which testify to the gas fluid discharge from greater depths [52]. Moreover, the coal-bearing beds of the Tankhoy Formation of the Oligocene-Miocene age in this part of the lake may serve as a source of gas for hydrates formation.…”
Section: Geological Setting Of Lake Baikal Sampling Sitesmentioning
confidence: 86%
“…The study of the southern basin included the sampling of sediments from the mud volcano Malenky (site 13, Figure 1, Table 1; [6,7,13,28,[48][49][50]) and gas hydrate-bearing sediments from the mud volcano Kedr (site 14, 15, Figure 1, Table 1; [49,51,52]). The former study of gas fluid from the MV Malenky [6] has suggested its possible migration from the deep strata.…”
Section: Geological Setting Of Lake Baikal Sampling Sitesmentioning
confidence: 99%